Analysis of STAD model on students with low abilities in learning geometry - Pahmi, Samsul; Priatna, Nanang; Yulianti, Karina; Nurulaeni, Fitria; Kumar, Akash Satish (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
This research is based on the mathematics learning outcomes of elementary school students which are still low in terms of student learning outcomes. The current study reveals that as many as 66.67% of students have not been able to achieve the minimum requirements, especially in the section of geometry; reflecting a need to improve mathematics learning outcomes. This gap in learning outcome is due to the fact that a majority of students tended to be passive during learning. The STAD learning model is a learning model that emphasizes student activities and interactions for learning mathematics in the classroom. The research design used in this study is a one group pretest posttest design. The sampling method used in the study was purposive sampling from a class of thirty elementary school students with issues related to mathematical abilities. Data collection techniques consist of primary sources in the form of tests, interviews, and observations, while secondary sources include documentation and literature studies. The data analysis technique used is the t-test (or using the Wilcoxon test if the data is not normally distributed), and the Gain Test. The results showed that there is a positive influence of STAD model on learning outcomes.